2017
DOI: 10.1242/jcs.206664
|View full text |Cite
|
Sign up to set email alerts
|

Maternal DCAF2 is crucial for maintenance of genome stability during the first cell cycle in mice

Abstract: Precise regulation of DNA replication and genome integrity is crucial for gametogenesis and early embryogenesis. Cullin ring-finger ubiquitin ligase 4 (CRL4) has multiple functions in the maintenance of germ cell survival, oocyte meiotic maturation, and maternal-zygotic transition in mammals. DDB1-cullin-4-associated factor-2 (DCAF2, also known as DTL or CDT2) is an evolutionarily conserved substrate receptor of CRL4. To determine whether DCAF2 is a key CRL4 substrate adaptor in mammalian oocytes, we generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The double DNA content per se may not be blamed for the 2-cell arrest of COPS3inactivated embryos, since tetraploid embryos form blastocysts 53 , whereas genotoxic stress (DNA damage) is well-known to cause 2-cell arrest 54 . Similar effects on DNA replication and repair in 2cell mouse embryos have previously been reported after genetic ablation of DDB1-and CUL4associated factor 2 (Dcaf2) and Cullin 1 (Cul1) [55][56][57][58] , however, the operating mode of COPS3 may or may not be the same. Whereas the inactivation of CUL1 resulted in an accumulation of pan-CYCLIN E 55 , the inactivation of COPS3 resulted in an accumulation of Cyclin E2 mRNA but not of Cyclin E1 mRNA; and whereas COPS3 features a cortical deposit in oocytes, this structure could not be demonstrated in Dcaf2-deficient oocytes (due to the lack of a suitable antibody) and the microinjection of mCherry-tagged Dcaf2 mRNA in oocytes did not result in the assembly of a cortical rim 56 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The double DNA content per se may not be blamed for the 2-cell arrest of COPS3inactivated embryos, since tetraploid embryos form blastocysts 53 , whereas genotoxic stress (DNA damage) is well-known to cause 2-cell arrest 54 . Similar effects on DNA replication and repair in 2cell mouse embryos have previously been reported after genetic ablation of DDB1-and CUL4associated factor 2 (Dcaf2) and Cullin 1 (Cul1) [55][56][57][58] , however, the operating mode of COPS3 may or may not be the same. Whereas the inactivation of CUL1 resulted in an accumulation of pan-CYCLIN E 55 , the inactivation of COPS3 resulted in an accumulation of Cyclin E2 mRNA but not of Cyclin E1 mRNA; and whereas COPS3 features a cortical deposit in oocytes, this structure could not be demonstrated in Dcaf2-deficient oocytes (due to the lack of a suitable antibody) and the microinjection of mCherry-tagged Dcaf2 mRNA in oocytes did not result in the assembly of a cortical rim 56 .…”
Section: Discussionsupporting
confidence: 56%
“…Similar effects on DNA replication and repair in 2cell mouse embryos have previously been reported after genetic ablation of DDB1-and CUL4associated factor 2 (Dcaf2) and Cullin 1 (Cul1) [55][56][57][58] , however, the operating mode of COPS3 may or may not be the same. Whereas the inactivation of CUL1 resulted in an accumulation of pan-CYCLIN E 55 , the inactivation of COPS3 resulted in an accumulation of Cyclin E2 mRNA but not of Cyclin E1 mRNA; and whereas COPS3 features a cortical deposit in oocytes, this structure could not be demonstrated in Dcaf2-deficient oocytes (due to the lack of a suitable antibody) and the microinjection of mCherry-tagged Dcaf2 mRNA in oocytes did not result in the assembly of a cortical rim 56 . Refining the mechanistic picture of the role of COPS3 in DNA metabolism, our study also indicated possible mediators of the nuclear DNA phenotype: Downregulation of genes such as Geminin and Brcc3, which superintend to DNA endoreduplication and DNA repair, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…Conditional (B cell) Impaired B cell maturity and development 256 Conditional (T cell) Insufficiency of T cells 257 Conditional (oocyte) Oocyte death and infertility 69,70 Conditional (oocyte) Female infertility 68 Dcaf2 −/− Substrate recognition protein Germline Susceptible to UV-induced skin carcinogenesis 76 Abbreviations: MDSCs: myeloid-derived suppressor cells; LPS: lipopolysaccharide; UV: ultraviolet;…”
Section: Substrate Recognition Proteinmentioning
confidence: 99%
“…While female reproduction remains normal in individual Cul4a −/− mice, abrogation of the entire CRL4 ubiquitin ligase led to infertility in females 67 . Interestingly, conditional deletion of Ddb1 or CRL4 substrate receptors VprBP/DCAF1 or DCAF2 cause female infertility possibly via diverse mechanisms including, massive DNA damage and disruption of the cell cycle, TET (Ten-eleven translocation methylcytosine dioxygenase) inactivation-mediated ovulation defects, oocyte loss, or repression on PI3K/Akt pathway [68][69][70] .…”
Section: Introduction Of Cullin 4 E3 Ligasesmentioning
confidence: 99%
“…They are known as DDB1-associated and cullin-4-associated factors (DCAFs) [8]. The in vivo functions of oocyte-derived DCAF1 and DCAF2 in mediating oocyte meiosis and zygotic genome stability have been reported [9,10]. By RNA interference (RNAi) screening in Caenorhabditis elegans, we found that a novel DCAF conserved from Schizosaccharomyces pombe to Homo sapiens plays an important part in oogenesis.…”
Section: Introductionmentioning
confidence: 99%